Perbandingan Manajemen Sekolah Biasa dengan Manajemen Boarding School - Fadilah, Ahmad Arif; Nurjanah, Fitria; Qurani, Fathiya Cahaya; Sefani, Nur Aliza; Wahyu, Rahma Rizkiya; Agustin, Renny; Asmoro, Shifa Nur; Septi, Syafani Mayang; Mulyaningsih, Yuni (MASALIQ, 2022)
Background is the focus of this study is the comparison of ordinary school management with boarding school management for improvement or additional management in schools so that it not only aims to improve the quality of learning and realize national education goals but also pay attention to education. wider Islam so that this generation becomes a generation with good character in accordance with the objectives of character education. The purpose to provide knowledge about the differences between ordinary school management and boarding school management which can later be reviewed for management improvement in schools so that they can improve the quality of schools by also paying attention to Islamic education. The method used is a type of library research, namely systematic activities related to the methods of collecting library data, reading it, writing and reviewing research materials. As a results There needs to be a new touch in the concept and practice of education management. The need for an increase in religious matters in ordinary school management in order to realize the goals of character education and the need for more attention and assistance with facilities for boarding schools. The conclusion is that proper management is needed to achieve educational goals in improving quality. Ordinary schools and boarding schools are all equally good places to gain knowledge, it's just a matter of reforming and realizing better school management by also increasing Islamic education for children who have good faith and character. That’s why to reach the dreams of the nation's children, it is necessary to improve facilities and highly qualified teaching staff.